Does Large Scale Infrastructure Investment Alleviate Poverty? Impacts of Rwanda's Electricity Access Roll-Out Program - Luciane Lenz; Anicet Munyehirwe; Jörg Peters; Maximiliane Sievert (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2015)
The United Nations' objective to provide electricity to the 1.3 billion people without access in developing countries comes at high costs. Little evidence exists on socioeconomic impacts of electrification. This paper rigorously investigates effects of a large grid extension program in Rwanda on all rural beneficiary groups: households, microenterprises, health centers, and schools. While the program has led to a tremendous increase of connections, appliance uptake and electricity consumption remain low. We find only weak evidence for impacts on classical poverty indicators. To inform future policy design, we call for thorough cost-benefit comparison between on-grid and off-grid solutions.
Keywords: O13; O18; Q41; 330; energy access; difference-in-differences; electrification; mixed-methods; Sub-Saharan Africa